Model Penilaian Kemampuan Bermain Sepakbola dalam Small Side Game bagi Pemain Usia Muda (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2017)
Penelitian ini merupakan penelitian pengembangan. Prosedur penelitian pengembangan yang digunakan meliputi; analisis produk yang akan dikembangkan, mengembangkan produk awal, validasi ahli, uji coba lapangan yang meliputi uji kelompok kecil dan uji kelompok besar, revisi produk, dan hasil produk pengembangan.Hasil penelitian ini adalah sebuah model penilaian kemampuan bermain sepakbola dalam small side game bagi pemain usia muda. Hasil perhitungan validitas instrumen menyatakan bahwa validitas sebesar 0,988. Hasil perhitungan uji instrumen keandalan data diketahui bahwa nilai reliabilitas sebesar 0,998.Simpulan bahwa; Produk penilaian kemampuan bermain sepakbola dalam small side game bagi pemain usia muda terbukti valid dan reliabel. Saran: (1) Pelatih sepakbola dapat menggunakan model penilaian ini untuk mengetahui tingkat kemampuan bermain pada pemain usia muda di sekolah sepakbola (SSB) yang dilatihnya. (2) Produk model penilaian ini dapat dijadikan sebagai referensi bagi pelatih sepakbola untuk mengembangkan produk lain dalam ruang lingkup evaluasi latihan sepakbola.Assessment is one of important things in a process of football practice process. Through this football ability assesment, coaches gained the right information about the progress of the players’ abilities. So the players' skills in playing football could be seen on the actual situation, and it was expected this activity could increase the model of practice evaluation.This was a developmental research. The development procedure used include; analysed the developed product, develop the initial product, experts validation, small group trials and field trials, product revision, and the results of product development. Results of this research were a football ability assessment model in small side games for young players. The result of instrument validity calculation stated that the validity 0,988. The results of instruments test data reliability, it was known that the value of reliability 0,998. Conclusion of this research was that a product of football ability assessment in small side games for young players was proved to be valid and reliable. It is suggested that: (1) Assessment model to determine the football ability level of the young players at Football School (2) This assessment model product is expected as a reference for the coaches to develop other products within the scope of football practice evaluation.